2002
DOI: 10.1034/j.1399-0004.2002.610111.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Xp duplication in a girl with dysmorphic features: the change in replication pattern of late‐replicating dupX chromosome

Abstract: In this paper we present the case of a girl at the age of 32 months with dysmorphic features, including general muscular hypotonia, developmental delay and mental retardation. The cytogenetic analysis revealed de novo partial duplication of Xp: 46,X,dup(X)(p11.23-->p22.33: :p11.23-->p22.33). To characterize the duplication, X painting, Kallman (KAL), yeast artificial chromosomes (YACs) and bacterial artificial chromosomes (BACs) covering Xp11.23-->Xp22.33 region were used. Selective inactivation of the abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…As with both males and females who have overlapping duplications of the proximal part of the short arm of the X chromosome our patient has an abnormal EEG [Nielsen and Langkjaer, 1982; Kokalj Vokac et al, 2002; Tzschach et al, 2008]. Mutations in many of the genes in the duplicated Xp segment in our patient have been associated with seizures (Table I).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…As with both males and females who have overlapping duplications of the proximal part of the short arm of the X chromosome our patient has an abnormal EEG [Nielsen and Langkjaer, 1982; Kokalj Vokac et al, 2002; Tzschach et al, 2008]. Mutations in many of the genes in the duplicated Xp segment in our patient have been associated with seizures (Table I).…”
Section: Discussionsupporting
confidence: 64%
“…X inactivation initially occurs at random, but in females with structural rearrangements of the X chromosome several factors will determine whether there is subsequent cell selection against the abnormal X. Duplications which are restricted to Xp11.2–Xp11.4 are generally associated with random patterns of X inactivation [Matsuo et al, 1999; Portnoi et al, 2000; Monnot et al, 2008], while females with larger overlapping duplications have been reported to have selective inactivation of the abnormal X [Nielsen and Langkjaer, 1982; Kokalj Vokac et al, 2002]. In contrast, X‐inactivation analysis in our patient showed that the normal X chromosome is inactivated in the majority of cells in DNA extracted from whole blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females who do not have skewed X‐inactivation can exhibit severe phenotypic abnormalities, similar to those seen in males with X chromosome duplications [Carrozzo et al, 1997; Matsuo et al, 1999]. Even when selective X‐inactivation does occur, several mechanisms may contribute to abnormal phenotypes in females with X chromosome duplications, including: (1) expression of recessive mutant genes on the active, nonduplicated X chromosome, (2) incomplete inactivation of the duplicated region [Kokalj Vokac et al, 2002], (3) tissue‐dependant X‐inactivation pattern, or (4) coincidental abnormalities independent of X chromosome aberrations [Aughton et al, 1993]. Additionally, since skewing occurs by cell selection after inactivation was established randomly, cells containing the active abnormal X chromosome could have deleterious effects before their elimination by the selection process [Monnot et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…We identified from the literature 10 patients who have either a karyotype 47,+ESAC(X), or another karyotype resulting in functional disomy of X chromosome genes [Nielsen and Langkjaer, 1982; Koch et al, 1990; Duncan et al, 1993; Silahtaroglu et al, 1995; Manea et al, 1997; Fritz et al, 1998; Tumer et al, 1998; Huang et al, 1999; Portnoi et al, 2000; Kokalj Vokac et al, 2002; Kolomietz et al, 2005; Bonnet et al, 2006; Musio et al, 2006]. The clinical details of these patients are summarized in Table I and the chromosome breakpoints shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%